Effects of ACEi and ARB on post-exercise hypotension induced by exercises conducted at different times of day in hypertensive men. (16th November 2020) - Brito, Leandro C.; Azevêdo, Luan; Peçanha, Tiago; Fecchio, Rafael Yokoyama; Rezende, Rafael Andrade; da Silva, Giovânio Vieira; Pio-Abreu, Andrea; Mion, Décio; Halliwill, John R.; Forjaz, Claudia L. M.
ABSTRACT: Background: Post-exercise hypotension (PEH) is greater after evening than morning exercise, but antihypertensive drugs may affect the evening potentiation of PEH. Objective: To compare morning and evening PEH in hypertensives receiving angiotensin-converting enzyme inhibitors (ACEi) or angiotensin II receptor blockers (ARB). Methods: Hypertensive men receiving ACEi (n = 14) or ARB (n = 15) underwent, in a random order, two maximal exercise tests (cycle ergometer, 15 watts/min until exhaustion) with one conducted in the morning (7 and 9 a.m.) and the other in the evening (8 and 10 p.m.). Auscultatory blood pressure (BP) was assessed in triplicate before and 30 min after the exercises. Changes in BP (post-exercise – pre-exercise) were compared between the groups and the sessions using a two-way mixed ANOVA and considering P < .05 as significant. Results: In the ARB group, systolic BP decrease was greater after the evening than the morning exercise, while in the ACEi group, it was not different after the exercises conducted at the different times of the day. Additionally, after the evening exercise, systolic BP decrease was lower in the ACEi than the ARB group (ARB = −11 ± 8 vs −6 ± 6 and ACEi = −6 ± 7 vs. −8 ± 5 mmHg, evening vs. morning, respectively, P for interaction = 0.014). Conclusions: ACEi, but not ARB use, blunts the greater PEH that occurs after exercise conducted in the evening than in the morning.